Strategi Inovasi Pengembangan SDM Aparatur di Era Digitalisasi BPSDMD Provinsi Banten - Gimas Rahadyan; Jeni Minan; Rizka Maulidina Sumita (HK-Publishing, 2025)
Local governments are required to adapt to electronic systems through the Electronic-Based Government System (SPBE) policy. The Human Resources Development Agency (BPSDMD) of Banten Province faces challenges regarding low digital literacy among civil servants, a conventional work culture, and limited network infrastructure. This study aims to assess the effectiveness of innovation strategies for civil servant human resource development in addressing these challenges, utilizing Chandler’s strategy theory and Bekkers’ digitalization framework. A descriptive qualitative approach was employed, involving interviews, observations, and document analysis. The results indicate that BPSDMD Banten Province successfully implemented blended learning and remote learning methods, alongside optimizing the